2022
DOI: 10.1145/3517384
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Concerns for Visual Assistance Technologies

Abstract: BoulderCCS Concepts: • Human-centered computing → Empirical studies in accessibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…P1 reflected on the lack of concerns as “we either got numb or gave up.” Such attitudes could be explained by their nuanced understanding of data policies. For example, camera-based assistive technologies like Aira or SeeingAI which our participants reported to use, provide no clear indication of whether and for what purpose personal visual data are shared with third parties [ 130 ]. This perhaps could lead to something of a paradox widely discussed in privacy literature [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P1 reflected on the lack of concerns as “we either got numb or gave up.” Such attitudes could be explained by their nuanced understanding of data policies. For example, camera-based assistive technologies like Aira or SeeingAI which our participants reported to use, provide no clear indication of whether and for what purpose personal visual data are shared with third parties [ 130 ]. This perhaps could lead to something of a paradox widely discussed in privacy literature [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brown [ 29 ] found that, despite the general worries people seemed to have about privacy, they would still give out information for perceived benefits. In fact, the two participants who reacted to both scenarios ( i.e ., potential risk cases of re-identification, data abuse and misuse) with stronger concerns and hesitancy to data sharing, reported to use Be My Eyes—one of the few services that explicitly indicates dissemination of video streams to third parties [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
“…To effectively train AI models for these varied use cases, it is crucial to create comprehensive datasets that reflect a wide range of scenarios, information display preferences, and output modalities. If these datasets will contain sensitive information pertaining to BLV people -for example, to capture the scenario of watching videos from friends and family -we must also recognize and consider BLV users' visual privacy concerns [46,112,113,137].…”
Section: Applying Generative Ai To Explore the Video Accessibility De...mentioning
confidence: 99%